(untitled) - Silver, Harvey F. (Upper Saddle River, N.J., 2009)
The Strategic Teacher offers a repertoire of strategies designed and proven to meet today's high standards and reach diverse learners. Twenty reliable, flexible strategies (along with dozens of variations) are organized into these groups of instruction: mastery style to emphasize the development of student memory; understanding style to expand students' capacities to reason and explain; self-expressive style to stimulate and nourish students' imaginations and creativity; interpersonal style to help students find meaning in the relationships they forge as partners and team members, united in the act of learning; and four-style strategies that integrate all four styles. To guide teachers in delivering content to students, the authors started with the best research-based teaching and learning strategies and created a tool called the Strategic Dashboard. The dashboard provides information about each teaching strategy in a concise, visual profile; it is also designed to document how one incorporates current, highly respected research into instructional plans.
Keywords: Effective teaching,Learning, psychology of,Lesson planning